EMOTIONAL BRANDING MODEL FOR THE LOYALTY OF HOSPITAL BRANDS OF THE CITY OF RIOBAMBA - Shaqui Pomaquiza, Marco Franklin; Naranjo Sánchez, Tatiana Karina; Montufar Guevara, Juan Carlos; Naranjo Vaca, Myriam Johanna (mktDESCUBRE; Vol 1 No 3 (2020): Special Edition 1st International Marketing Congress, 2020)
Emotional branding is an elementary factor for any company, but at the hospital level the necessary importance has not been taken, which is why traditional methods have been used, which are not necessary to make the brand reach the unconscious and persuade the users. The objective of the investigation is to establish the appropriate model that allows to manage in a better way all the parameters to design a brand model that motivates the clients to choose to acquire the hospital service in the city of Riobamba. The analysis is based on a deductive method to reach a specific point, thus taking into account public and private hospitals that offer similar specialties. Through the Eye Tracking biometric equipment, more truthful data is obtained that allows to know the exact points of fixation and thus give possible modifications to a brand structuring model. The Master Brand model is established as a customer loyalty agent, the features that make up the model improves efficiency and quality of service, which leads to the creation of somatic markers in the minds of hospital users.